100 YEARS OF SUPERCONDUCTIVITY (1911-2011) - Akhtar, M. J. (The Nucleus, 2011)
In 1911 superconductivity was discovered in mercury having transition temperature at 4.2 K, during last 100 years transition temperature has been increased to 153 K. In this manuscript the major developments in experimental and theoretical fields have been reviewed. A summary of various applications of superconducting materials is also given and future prospects of superconductivity are discussed.